Cryo-fixation by self-pressurized rapid freezing - Grabenbauer, Markus; Han, Hong-Mei; Hübinger, Jan (Electron microscopy, 2014)
High-pressure freeze fixation is the method of choice to arrest instantly all dynamic and physiological processes inside cells, tissues, and small organisms. Embedded in vitreous ice, such samples can be further processed by freeze substitution or directly analyzed in their fully hydrated state by cryo-electron microscopy of vitreous sections (CEMOVIS) to explore cellular ultrastructure as close as possible to the native state. Here, we describe the procedure of self-pressurized rapid freezing as fast, easy-to-use, and low-cost freeze fixation method, avoiding the usage of a high-pressure freezing (HPF) apparatus. Cells or small organisms are placed in capillary metal tubes, which are tightly closed and plunged directly into liquid ethane cooled by liquid nitrogen. In parts of the tube, crystalline ice is formed and builds up pressure sufficient for the liquid-glass transition of the remaining specimen. The quality of samples is equivalent to preparations by conventional HPF apparatus, allowing for high-resolution cryo-EM applications or for freeze substitution and plastic embedding.